Jean Braithwaite, ed. Chris Ware: Conversations. Jackson: The UP of Mississippi, 2017. - Lindsay Harper Cannon (Studies in 20th & 21st Century Literature, 2017)
Review of Jean Braithwaite, ed. Chris Ware: Conversations. Jackson: The UP of Mississippi, 2017.
Keywords: Chris Ware; comics; popular culture; creative process